Optimizing the structure of scanning probes for atomic manipulation - Møller, Morten (2017)
Scanning probe microscopy (SPM) allows us to directly measure the interactions between a probe and a sample at the atomic scale. Techniques such as non-contact atomic force microscopy (NC-AFM), allows us to to characterize the forces present on a surface, resolve the atomic structure of molecules or examine their chemical properties, while scanning tunneling microscopy (STM) allows their electronic properties to be characterized. As the interactions take place at the atomic scale, the atomistic state of the probe apex plays a crucial role. In AFM, it is the atomic scale forces between the outermost atoms of the probe and surface that are dominant, while for STM the density of states (DOS) that contribute to tunneling are crucial. Therefore, understanding and controlling the tip termination is crucial to derive meaningful interpretations from experimental data. In this thesis, the role of the tip termination is examined for various surfaces and situations. We find that determining the "right" tip state depends critically on the experiment and several general strategies for shaping the tip apex into a preferred state are therefore outlined. H:Si(100) surfaces were used as a substrate for lithographic patterning using STM. We have successfully implemented an automated extraction routine for performing large scale patterning with high fidelity and single atom specificity. Our ultimate goal is to combine the extraction routine with SPM image recognition software to allow analysis and manipulation of atomic scale features without human intervention. To perform manipulations reliably, the tip influence on "what we see" (tip imaging states), or specifically on what the recognition software can identify, needs to be considered. We find, counter-intuitively, that atomic scale manipulation with the highest fidelity occurs when silicon dimers are observed as rows as opposed to when atomic resolution imaging occurs. The tip state influence on measuring surface diffusion of PTCDA on Ag(110) surfaces, was also investigated. We find that the adsorption kinetics of diffusing molecules can only be detected for specific tip imaging states. To allow examination with no-human intervention, the tip state needs to be carefully considered, and a combination of analytical and spectroscopic tools needs to be implemented in conjunction with the experiment. Additionally, characterization of the tip apex was investigated at the tunnel junction between a STM tip and a metal surface using field emission measurements. Our results suggest that field emission measurements performed at the tunnel junction are sensitive to changes in the nanoscopic/mesoscopic tip apex structure, thus opening up the possibility of automating the process of characterization the tip apex.